Ruling England 1042-1227 - Huscroft, Richard, author. Link
1 online resource (xxxiv, 278 pages)
Keywords: Since its first publication in 2005, Ruling England has established itself as an authoritative account of English politics and the growth of royal power from 1042. Using chronicle and administrative records, it focuses on the aims and priorities of the kings of England and on how and why the systems which established and enhanced their authority developed during this period. It explores how the machinery of government worked and grew, and how the legal system evolved to consolidate royal control over the kingdom. It also explores the contribution of the English Church to politics and how the partnership between king and clergy was crucial to the consolidation of royal power. Now in its third edition, Ruling England is a key text for students wishing to understand the complexities of medieval kingship in England from 1042 to 1227. It has been expanded chronologically to cover the minority of King Henry III and there are more extensive treatments of the interactions between the rulers of England and their British neighbours, the role of women in English politics during this period and of the place in society occupied by England⁰́₉s Jewish communities.